Comparison of the Gut Microbiota in Healthy Infants With Different Delivery Modes and Feeding Types: A Cohort Study - Ma, Jingran; Li, Zhenghong; Zhang, Wenjuan; Zhang, Chunli; Zhang, Yuheng; Mei, Hua; Zhuo, Na; Wang, Hongyun; Wu, Dan (Frontiers in Microbiology, 2022)
To compare the gut microbiota of healthy infants based on specific interactions of delivery modes and feeding types, we recruited 62 healthy babies who were followed up for 2 years from our previous cohort study of 91 infants (the rest were lost to follow-up). They were exclusively fed breast milk or specific formulas for more than 4 months after birth. The fecal bacterial composition was tested at 40 days, 3 months and 6 months of age. Solid foods were introduced from 4 to 6 months of age and thus did not affect the microbiota before 4 months of age. According to the different delivery modes (vaginal delivery, VD, or cesarean section delivery, CS) and feeding types, the infants were assigned to four different groups: VD-br (breast-fed), VD-fo (formula-fed), CS-br, and CS-fo groups. We found that at 40 days of age, the α diversity (reported as the Shannon index) was lower in the breastfed infants than in the formula-fed infants. At 3 months of age, the α diversity was significantly lower in the CS-br group, although significant differences were not observed after solid food introduction. Bifidobacterium represented the most predominant genus in all groups at all time points, followed by Enterobacteriaceae. At 40 days of age, the abundance of Bifidobacterium was much higher in the CS-br group than in the CS-fo group but did not differ between the VD-br and VD-fo groups. The differences in Bifidobacterium disappeared at 3m and 6m among the different groups. At 40 days of age, the abundance of Streptococcus and Enterococcus was much lower in the breastfed infants than the CS-fo group. At 3 months of age, Enterococcus was significantly lower in the CS-br group than in the formula-fed infants, although for infants delivered by VD, the difference between feeding types was not significant. The specific interaction of delivery modes and feeding types has a large impact on the infants’ gut microbiota. Breastfeeding and vaginal delivery may decrease the potential adverse effects of formula feeding or cesarean section delivery on gut microbiota, thus lead to a more stable and beneficial gut environment for infants.